V.V. Nikitin – a pragmatist of archaeology - Sergey V. Kuzminykh; Aleksandr A. Vybornov; Tatyana B. Nikitina; Aleksei N. Sorokin (Археология евразийских степей, 2025)
The article is dedicated to the memory of V.V. Nikitin, one of the prominent Russian specialists in the field of primeval archaeology. For a native of Western Ukraine, the Mari region became a second homeland, and the study of the antiquities of the Middle Volga region from the Stone Age to the Early Metal Era - spanning an entire lifetime - became his most significant contribution to national archaeological science. Thanks to V. V. Nikitin's exploratory searches, the register of historical and cultural monuments of the Republic of Mari El has been enriched by more than 500 archaeological sites from various eras. His research on the Mesolithic, Neolithic, and Eneolithic monuments of the Mari Volga region enriched Soviet and Russian archaeology by addressing the most complex issues of cultural genesis among prehistoric communities in the forest zone of Eastern Europe, their socio-economic development, and ethnocultural history. At the same time, Valery Valentinovich was never a "pure" theorist, he always remained a pragmatist – a field researcher focused on discovery, in the process of which the meticulous study of sources was paramount to him. Perhaps this is his greatest legacy to his students and followers.